Adult Burkitt lymphoma: An institutional experience with a uniform chemotherapy protocol - Patekar, Mukesh; Gogia, Ajay; Tiwari, Akash; Kumar, Lalit; Sharma, Atul; Mallick, Soumya Ranjan; Sharma, Mehar Chand; Thulkar, Sanjay; Gupta, Ritu (South Asian Journal of Cancer, 2018)
Background: Burkitt lymphoma (BL) is treated with short, intensive, noncross resistant multidrug chemotherapy regimens. The management of this aggressive lymphoma is a challenge in our resource-limited setting, and the published data from India is scarce. Aim: This retrospective study aims to evaluate the clinical features and treatment outcomes in adult patients with BL treated with uniform chemotherapy, cyclophosphamide, vincristine, doxorubicin, methotrexate, ifosfamide, etoposide, cytarabine (CODOX-M/IVAC) protocol (± Rituximab). Materials and Methods: The hospital records between 2011 and 2017 were reviewed to identify adult patients (age ≥18 years) who were treated with CODOX-M/IVAC protocol (± Rituximab). The demographic and clinical details, treatment, outcomes, and toxicity were recorded from the patient's prospectively maintained case records. Results: Eighteen patients were included in this study. The median age was 38 years with male:female ratio 3.5:1. The majority of patients were high risk (14/18). All patients had extranodal site of involvement. The treatment completion rate was 83.3%. The overall response rate = 77.8% including complete response rate = 66.7%. Five patients (27%) had progressive disease on therapy. The estimated 2-year overall survival and event-free survival were 73% and 68.4%, respectively. The most common toxicity was myelosuppression (grade v3/4 neutropenia = 88.8%, grade 3/4 thrombocytopenia = 77.7%, and grade 3/4 anemia = 66.6%), febrile neutropenia was seen in 66.6% cases. Most common nonhematological toxicity was mucositis (grd3/4 = 33.3%). No toxic death was seen. Conclusion: This one of the first retrospective analyses of treatment outcomes from India suggests that our patients are demographically and clinically similar to the western counterpart. The treatment completion rate is high despite significant toxicity. BL has a good outcome if treated adequately.
Keywords: Burkitt lymphoma; cyclophosphamide; cytarabine/uniform protocol/treatment; doxorubicin; etoposide; ifosfamide; methotrexate; outcome; vincristine